Bilayered arcade-like scaffolds for articular cartilage repair - Semitela, Â. (2022)
Articular cartilage is a highly organized tissue that it is adapted to the complex mechanical loading in joints. Given the limited self-healing of this tissue, tissue engineering (TE) strategies have explored the development of 3D anisotropic fibrous scaffolds with the implementation of specific mechanical stimulus. However, this functionally is dependent on the ability to recreate the depth-dependent collagen fibre alignment on the 3D fibrous scaffolds, which has been considerably challenging. In this work, bilayered structures with different fibre orientations were fabricated via polycaprolactone and Gelatin electrospinning and polyethylene glycol (PEG) particles electrospraying. After PEG removal, large interfibre spaces were created, that were compatible with chondrocyte migration The in vitro studies confirmed the biocompatibility of the scaffolds and their ability to guarantee cell attachment and migration through the scaffold. The mechanical stimulation applied through unconfined compression substantially improved chondrocyte response. These results confirmed the potential of the developed 3D bilayered scaffolds for articular cartilage TE.